Tolerance of various legume cover crops to pre- and post-emergence herbicides - Gómez Gómez, Robin (2022)
Introduction. Cover crops compete during their initial growth stages with weeds, therefore in areas where the predominant weeds are fast growers it is necessary to spray herbicides to control those plants while the cover gets established. Objetive.  To evaluate the tolerance of the legumes  Mucuna pruriens (L) DC cv. preta, M. pruriens cv. cinza, Vigna radiata (L.) Wilczek, Pueraria phaseoloides (Roxb) Benth. and Crotalaria spectabilis Roth to pre- and postemergence herbicides. Materials and methods. Two studies were carried out in a greenhouse of the University of Costa Rica, located in Alajuela, Costa Rica. The first experiment evaluated the postemergence herbicides clethodim, fluazifopp-butyl, fomesafen and bentazon in 2012 and was repeated in 2013. The second experiment was performed twice in 2014 to evaluate the postemergence herbicides pendimethalin, oxyfluorfen, alachlor and linuron. Plant height, injury index and dry weight of plants sowed in 1.5 liters pots was assessed. The experimental design was completely randomized. Results. All the evaluated species, except for P. phaseoloides, were tolerant to bentazon, cletodim and fluazifop-p-butil. These species were also tolerant to alachlor, linuron, and pendimethalin. P. phaseoloides was tolerant to fomesafen and fluazifop-p-butyl, but resulted moderately affected by the preemergent herbicides. Only plants treated with oxyfluorfen and fomesafen showed a significant dry weight reduction, except for P. phaseoloides plants sprayed with fomesafen. Conclusion. The evaluated legumes were tolerant to the majority of the sprayed herbicides for the control of both dicotyledonous and monocotyledonous weeds.